Given:
Polynomial is [tex]3x^2+15x-56[/tex].
To find:
The sum of given polynomial and the square of the binomial (x-8) as a polynomial in standard form.
Solution:
The sum of given polynomial and the square of the binomial (x-8) is
[tex]3x^2+15x-56+(x-8)^2[/tex]
[tex]=3x^2+15x-56+x^2-2(x)(8)+8^2[/tex] [tex][\because (a-b)^2=a^2-2ab+b^2][/tex]
[tex]=3x^2+15x-56+x^2-16x+64[/tex]
On combining like terms, we get
[tex]=(3x^2+x^2)+(15x-16x)+(-56+64)[/tex]
[tex]=4x^2-x+8[/tex]
Therefore, the sum of given polynomial and the square of the binomial (x-8) as a polynomial in standard form is [tex]4x^2-x+8[/tex].